INTEGRASI FUNGSI-FUNGSI ADMINISTRASI PENDIDIKAN DALAM PENGELOLAAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Zulkia Sabrina (CV JK Riset Publishing Group, 2026)
This study examines the integration of educational administration functions in the management of Islamic Religious Education (IRE) learning in schools. The background of this research departs from the weak coordination between the functions of planning, organizing, implementing, and supervising the IRE learning process. The purpose of this study is to analyze how the integration of educational administration functions can improve the quality of IRE learning management. The method used is descriptive qualitative research with a case study approach in three junior high schools in Lampung. The results show that the systematic and planned integration of administrative functions contributes significantly to increasing the effectiveness of IRE learning, especially in the aspects of curriculum planning and learning evaluation. The study concludes that quality IRE learning management requires synergy between all educational administration functions in an integrated and sustainable manner.